Digital Transformation and New Methods of Sociological Research - Meshcheryakova, Nataliya N.; Rogotneva, Elena N. (KnE Social Sciences, 2021)
Today, digital transformation assists us to search for information on the Internet, to digitize data, to store and broadcast it conveniently; however, digital transformation changes not only the quality of technologies, but also the social reality, the structure of society, the ways of social interactions, the social actor, and research methods. Four breakthrough technologies — cloud computing, big data, artificial intelligence, and the Internet of things — determine the direction of these changes. The question is how sociology may use these technologies for its own purposes. In this paper, the outdated approaches of authorities are considered in relation to the monitoring criteria they use to evaluate their activities. We emphasize the potential to obtain representative data by using traditional survey methods. Nevertheless, changes in the socio-psychological characteristics of respondents actualize the transition from mass surveys to big data analysis and force us to replace directly posed questions with the indirect confirmation of hypotheses. The new technologies open greater opportunities for building correlations, identifying hidden patterns, and making predictions than it was possible till now. Thus, we need scientifically based coherent patterns across individual factors in order not to see cause-and-effect relationships in random matches. Research community has to develop these patterns. Keywords: Digital Transformation, Big Data, Cloud Computing, Artificial Intelligence, the methods of sociological research